AWARENESS OF CLIMATE CHANGE AMONG POULTRY FARMERS IN WESTERN ZONE OF BAUCHI STATE, NIGERIA AWARENESS OF CLIMATE CHANGE ADAPTATION STRATEGIES AMONG POULTRY FARMERS IN WESTERN ZONE OF BAUCHI STATE, NIGERIA - Bashir, U. A.; Garba, M.; Hassan, A. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the awareness of climate change adaptation strategies among poultry farmers in Western Zone of Bauchi State, Nigeria. A multi-stage sampling technique was used in selecting 120 respondents. Data were collected using structured questionnaire and analyzed using descriptive statistics and linear regression. The findings show that a substantial proportion (46.7%) of the respondents were within the ages of 28-40 years with a mean age of 36 years. Half (50.8%) of the respondents had tertiary level of education and majority (76.7%, 76.7%) rear chicken and had a flock size of 200 birds respectively. Majority (83.3%) of the respondents were aware of climate change and the major adaptation strategies used to mitigate climate change were trees planting (=4.4), access to information on climate and weather (=4.3), provision of ventilated houses (=4.2), provision of better hygiene (=4.2), and creating space (=4.1). The result from linear regression revealed that age and sex were negative and significant (P<0.05) factors influencing respondents’ awareness on climate change effect on poultry birds. It can be concluded that majority of poultry farmers were aware of climate change. In addition, Age and flock size were the major factors influencing the adoption of climate change mitigation strategies. It is recommended that there is need to intensify awareness campaigns to poultry farmers on how to mitigate the effects of climate change on poultry production.